Decentralised internet governance: the case of a 'peer-to-peer cloud' - Francesca Musiani (Internet Policy Review, 2014)
This article retraces the early stages of development of the 'peer-to-peer cloud' storage service Drizzle, with the aim of providing an example of decentralised network architecture as internet governance 'in practice'. More specifically, this paper sheds light on how changes in the architectural design of networked services affect the circulation, storage and privacy of data, as well as the rights and responsibilities exerted by different actors on them. This article does not mean to be a compendium of the implications of the decentralisation option in building a cloud platform, which entails a number of technical complications as well as advantages, including how to ensure the reliability and redundancy of data, and the soundness of the encryption mechanism. However, the privacy-related design choices described here are some of the many possible ways to illustrate the extent to which changes in network architecture are, indeed, changes in network governance.
Keywords: 300; Internet governance; Science and technology studies (STS); Peer-to-peer (P2P); Decentralisation; Privacy by design; Internet architecture; Cloud